Impact of Water Injection System on Diesel Engine Brake Power and Exhaust Emissions - Salih, Sabir M.; Mustafa, Eihab A. Raouf (Gezira Journal of Engineering and Applied Sciences, 2012)
A series of experiments were carried out to study and clarify the effect of Water Injection system ( WI ) on diesel engine performance and exhaust gas emissions (Nitrogen Oxides, Sulfur Dioxide, and Carbon Monoxide). The results obtained showed that, water injection increases the power output of the engine. Adding water to the incoming air allows for greater charge density. The water absorbs a large amount of heat as it vaporizes, thus reducing peak temperature and Nitrogen Oxides (NO X ) emissions. WI also decreases the emissions of Sulfur Dioxide (SO 2 ); the presence of water converts some of SO 2 gas into sulfuric acid (H 2 SO 4 ). Similarly, WI system was found to decrease the emissions of Carbon Monoxide (CO).